Human-Centred Autonomous Shipping - Lützhöft, Margareta; Earthy, Jonathan (Taylor & Francis, 2024)
Tracing the development of autonomous and automated shipping from a hype of unmanned ships to a more realistic use of automation to augment humans in maritime operations, this book shows why human factors and human-centred design are essential to the endeavour. Themes addressed in the book include technology and cybersecurity, regulation and classification, and competence and skills. It combines commentary and insight from experts across the industry as well as academia and describes a roller-coaster ride from conceptual idea via a period of hype where technologists and engineers enthusiastically advocated a rapid development as many others in the maritime industry felt compelled, but struggled, to follow and finally to a more measured view as cumulative experience started to show the limitations, risks, and the lack of a generic business case. This book is intended for anyone working in, researching in, or simply interested in shipping and the maritime domain and the evolution of autonomous shipping. The target audience includes regulators, educators, researchers, engineers, and manufacturers. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license